IDEATIONAL, INTERPERSONAL, AND TEXTUAL FUNCTION IN "THE COP AND THE ANTHEM" THROUGH A FUNCTIONAL STYLISTIC LENS - R, Hasan (Economics and Statistics Research Journal (ESRJ), 2023)
This paper utilizes the framework of Systemic Functional Linguistics (SFL) to conduct a functional stylistic analysis of O. Henry's short story "The Cop and the Anthem." The study explores the three meta functions of language: ideational, interpersonal, and textual, and their influence on the story's language expression characteristics, plot setting, and total cohesion. The paper aims to provide a reference for future functional stylistic analyses of similar short stories. The methodological approach involves addressing the research questions RQ1: How does the short story The Cop and the Anthem reflect Ideational Function of SFL; RQ2: How does the short story The Cop and the Anthem reflect Interpersonal Function of SFL; and RQ3: How does the short story The Cop and the Anthem reflect Textual Function of SFL. The analysis focuses on the transitivity structure of the text and selected sentences while identifying and examining the essential components of the story such as material, relationship, psychology, behavior, existence, and speech processes. The paper contributes to the understanding of the deeper meaning of the story through a functional stylistic approach, beyond its humor and artistic qualities